(untitled) (Research, Society and Development, 2022)
The State of Pernambuco develops public policy for school transportation, whose existence (or lack thereof) has a direct impact on the simplest level of the opportunity to attend school. Therefore, given the importance of this service, it is important to know how the state of Pernambuco is basing and organizing, for implementation and/or innovation of these policies. Starting from the conception of innovation as a rethinking in the current operationalization of these services either internally or externally, this research proposes to identify the instruments of innovations (or the lack of them) in the management of school transportation services in Pernambuco. As for the methodological procedures, the research is a descriptive exploratory study of qualitative approach, whose sources of information considered are the existing control instruments in the Management of Municipal Articulation of the State Secretariat of Education and Sports in the period 2017-2020, in the form of documents, spreadsheets, graphs, reports and tables. As for the management of school transport services in Pernambuco, innovation was emphasized in a broad perspective, having as a basis the knowledge connected with the interactive processes through which knowledge is created, exchanged, inter and intrainstitutionally, based on the principles of innovation strengthening the design of the public policy of public school transport, Therefore, it is emphasized the importance of public policy in the lives of students and how we must observe all the context that surrounds it, so that we have a fairer and more transparent State.